Challenges of providing health services to patients with cardiovascular diseases during disasters in Iran: A qualitative study - Shandiz Moslehi; Fahimeh Barghi Shirazi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Cardiovascular diseases are the most common causes of death in the world. Because of the rate of emergencies and disasters in the country, this study was conducted to investigate the challenges of providing health services to cardiovascular patients in emergencies and disasters in Iran. MATERIALS AND METHODS: This conventional content analysis study was conducted in 2020. Subjects were selected from among 16 Iranian experts) epidemiologists, cardiologists, PhD in Disaster Health, and PhD in Nursing (using purposeful and snowball sampling methods. Data were collected using semi-structured interviews and were analyzed by the content analysis. RESULTS: The results were obtained after analyzing the data in the pre-emergency phase (lack of training on medication and nutrition, lack of training vulnerable groups, lack of databases of cardiovascular patients, and lack of identification of patients before disasters), the emergency response phase (lack of sleep and rest patterns, lack of health forces, lack of blood pressure control, lack of proper nutrition, increased medication needs, and lack of mental health interventions), and the post-emergency phase (lack of planning, lack of management of patients' mental problems). CONCLUSION: Developing strategies for planning, training, providing resources, and mental health during the three phases of the emergency management cycle for specific groups such as cardiovascular patients together with empowering these patients in the event of disasters is one of the key strategies which can be used after curbed emergencies and disasters to reduce the rate of mortality.